Between Statutory Authority and Administrative Discretion: Case Study of the Merah Putih Cooperative Deed Made by a Notary - Pratiwi, Premitha Ayu; Siboy, Ahmad; Parmono, Budi (Fakultas Hukum Universitas Hang Tuah, 2026)
This study examines the normative conflict between statutory authority and administrative discretion in the establishment of Merah Putih Cooperatives under Indonesia’s 2025 national cooperative revitalization program. While the Law on the Notarial Office grants notaries general authority to prepare authentic deeds, administrative regulations require a specific designation as Cooperative Deed Officials (NPAK), creating legal uncertainty in practice. Unlike previous studies that focused on general cooperatives and the procedural role of NPAK, this research is the first to analyze the legal bottlenecks generated by state-driven digital transformation through the SABH/AHU Online system within the Merah Putih initiative. Using a normative juridical approach, this study evaluates the civil, administrative, and ethical consequences of deeds prepared by non-NPAK notaries. The findings demonstrate that although such deeds remain civilly valid, administrative rejection may prevent cooperatives from obtaining legal entity status, resulting in significant socio-economic losses at the village level. The findings reveal that digital administrative filtering has transformed ministerial discretion into de facto statutory limitation, generating legal uncertainty, delaying village economic programs, and causing measurable financial losses at the local level. This study proposes regulatory harmonization to restore statutory authority while maintaining administrative oversight. The policy implication emphasizes the need to prevent digital governance mechanisms from undermining hierarchical legal certainty in Indonesia’s cooperative development framework. This research offers policy recommendations for harmonizing statutory and administrative norms to ensure legal certainty, professional integrity, and the effective implementation of Indonesia’s cooperative reform agenda.